Peningkatan Prestasi Belajar Matematika melalui Pembelajaran Discovery Learning dengan Adaptasi Lesson Study - Ahmad Nafi'ul Abror; Dani Fernanda; Ira Rismawati; Feriyanto Feriyanto (AIJER: Algazali International Journal Of Educational Research, 2022)
Abstract: Improving Mathematics Learning Achievement through Learning Discovery Learning with Lesson Study Adaptation. The purpose of this study is to determine the application of the Lesson Study-Based Discovery Learning learning model to improve mathematics learning outcomes on the subject of Trigonometric Identity in class XI MIPA 4 semester 1 SMA Negeri 1 Gondang students for the 2022/2023 academic year. This research method uses a descriptive type of research using a qualitative approach. The subjects in this study were 34 students of class XI MIPA 4 SMAN 1 Gondang Mojokerto. The application of research is designed in accordance with the Lesson Study which consists of three stages, namely planning (Plan), implementation (Do), and evaluation (See). By using  the Discovery Learning Based Lesson Study learning model  , it can improve mathematics learning outcomes on the subject of Trigonometric Identity in class XI MIPA 4 semester 1 SMA Negeri 1 Gondang students for the 2022/2023 school year. This increase can be seen from the average score obtained by students, which is 70.60 on UH1, then increases to 81.78 on UH2. Keywords:  mathematics learning, discovery learning, lesson study